EFEKTIVITAS SISTEM INFORMASI AKUNTANSI PENJUALAN DAN PENERIMAAN KAS PADA HOTEL SANTIKA SUKABUMI - Nurlaelasani, Ela; Sulaeman, Sulaeman (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2023)
The purpose of this study was to analyze the effectiveness and application of the accounting information system for sales and cash receipts used by Hotel Santika Sukabumi. The method used in this research is a descriptive qualitative method with in-depth analysis. The type of data used in this research is secondary data, namely data generated from the process of interviews and observations with sources directly. The results of this study show that the application of the accounting information system for sales and cash receipts at Hotel Santika Sukabumi can provide information for company leaders through the system implemented, namely the Front Office System (FOS). The accounting information system for sales and cash receipts at Hotel Santika Sukabumi has been running effectively. This is characterized by the suitability of procedures in the application of accounting information systems for sales and cash receipts.